2001
DOI: 10.1542/peds.108.2.e22
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Pediatrician Practices in Retrieving Statewide Authorized Newborn Screening Results

Abstract: ABSTRACT. Objective. Mandated state newborn screening programs for the approximately 4 million infants born each year in the United States involves the following 5 components: 1) initial screening, 2) immediate follow-up testing of the screen-positive newborn, 3) diagnosis confirmation (true positive versus false positive), 4) immediate and long-term care, and 5) evaluation of all of the components of the system, including process and outcomes measures. Smooth functioning of this system requires pretest educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 2 publications
2
23
0
Order By: Relevance
“…However, a seamless system is not always the case, as illustrated in a study by Desposito et al 5 This study indicated that 31% of pediatricians were notified of screen-positive results Ͼ10 days after testing was completed. Although the majority of these patients received treatment and follow-up by the birth hospital or the state newborn screening follow-up team in a timely manner, communication with the primary care physician was less efficient than recommended guidelines.…”
mentioning
confidence: 99%
“…However, a seamless system is not always the case, as illustrated in a study by Desposito et al 5 This study indicated that 31% of pediatricians were notified of screen-positive results Ͼ10 days after testing was completed. Although the majority of these patients received treatment and follow-up by the birth hospital or the state newborn screening follow-up team in a timely manner, communication with the primary care physician was less efficient than recommended guidelines.…”
mentioning
confidence: 99%
“…Neonatal screening is a system of five stages that is habitually organized and carried out by the public health system, which has the resources and authority necessary to carry out universal screening, and in which pediatricians play an important role. 2,13,14,17,[19][20][21] The first step is to carry out the screening tests themselves. The objective is to achieve universal screening, i.e., all newborn infants should be screened.…”
Section: The Concept Of Neonatal Screeningmentioning
confidence: 99%
“…The policy that no news is good news must not be adopted. 20 Performing screening arouses expectations in families and they have the right to know the results as quickly as possible.…”
Section: The Concept Of Neonatal Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 8 found that state newborn screening programs do not always include pediatricians in the newborn screening communication process. Desposito et al 9 found that 31% of pediatricians were notified of screen-positive results Ͼ10 days after testing was completed. Public health agencies, which are facing the challenges of addressing an increasing number of threats to children's health (such as obesity and violence), need to work collaboratively with families and clinicians to gather and to share information for monitoring and health-promoting activities.…”
mentioning
confidence: 99%